2022
DOI: 10.3389/fpubh.2022.883177
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourced Data for Physical Activity-Built Environment Research: Applying Strava Data in Chengdu, China

Abstract: The lack of physical activity has become a rigorous challenge for many countries, and the relationship between physical activity and the built environment has become a hot research topic in recent decades. This study uses the Strava Heatmap (novel crowdsourced data) to extract the distribution of cycling and running tracks in central Chengdu in December 2021 (during the COVID-19 pandemic) and develops spatial regression models for numerous 500 × 500 m grids (N = 2,788) to assess the impacts of the built enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Fifth, contrary to the results of some studies that enterprises promote running activities (Yang et al, 2022b), in most areas, such as Shuhan Road and Balizhuang, enterprises harm running activities. It may be attributed to the job-housing imbalances among Chengdu residents.…”
Section: Control Variables In the Running Index Gwr Modelmentioning
confidence: 63%
See 1 more Smart Citation
“…Fifth, contrary to the results of some studies that enterprises promote running activities (Yang et al, 2022b), in most areas, such as Shuhan Road and Balizhuang, enterprises harm running activities. It may be attributed to the job-housing imbalances among Chengdu residents.…”
Section: Control Variables In the Running Index Gwr Modelmentioning
confidence: 63%
“…With the development of information and communication technology, crowdsourcing data such as Strava data emerged, which provides technical support for measuring the spatial distribution of PA on large sample sizes (Yang et al, 2022b). Moreover, many researchers have found that streets play an important role in the promotion of physical activities such as running and cycling (Lu et al, 2018b;Yang et al, 2021a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, to address the adverse effects of “Transit-Induced Gentrification” on urban vibrancy, we call for efforts to develop and improve the multi-level housing support system (e.g., government-subsidized and affordable rental housing) in the MSA to achieve a systematic spatial match for the “housing-transportation” system. This will help reduce the “Spatial Deprivation” suffered by low-and middle-income residents due to high housing prices ( 71 ), thus contributing to the development of equitable, accessible, and vibrant TOD communities. Finally, to accommodate the daily activities of young adults, urban planners need to improve the quality of public space in the high employment density MSA by providing adequate leisure facilities like small community parks.…”
Section: Discussionmentioning
confidence: 99%
“…This article takes Chengdu, the largest metropolis in western China and the capital of Sichuan province, as a case study. The city is in a period of fast industrialization and urbanization, and the land use pattern is changing substantially (Wei, X., Duan, L. 2021;Yang et al, 2022a;Yang et al, 2022b). As the first proposed park city and a low-carbon pilot city approved by the state, Chengdu is taking the lead in laying out low-carbon industries and carrying out carbon reduction actions in order to achieve the goal of carbon peak and carbon neutrality.…”
Section: Literature Reviewmentioning
confidence: 99%